Особенности течения процессов регенерации травмы слизистой ротовой полости крыс, развивающейся на фоне гиперчувствительности замедленного типа = Features during the process of regeneration of oral mucosa injury rats, develops on the background of delayed type hypersensitivity - Pochtar, V. N. (Journal of Education, Health and Sport, 2016)
Pochtar V. N. Особенности течения процессов регенерации травмы слизистой ротовой полости крыс, развивающейся на фоне гиперчувствительности замедленного типа = Features during the process of regeneration of oral mucosa injury rats, develops on the background of delayed type hypersensitivity. Journal of Education, Health and Sport. 2016;6(6):579-586. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56699 http://ojs.ukw.edu.pl/index.php/johs/article/view/3645 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Особенности течения процессов регенерации травмы слизистой ротовой полости крыс, развивающейся на фоне гиперчувствительности замедленного типа В. Н. Почтарь Украинский НИИ стоматологии НАМН Украины Резюме Автор провела экспериментальное исследование особенностей репарационных процессов слизистой щеки у 60 крыс с гиперчувствительностью замедленного типа. Результаты исследований показали, что репарационные процессы меняются по отношению к контролю: пролиферативная активность выше, а дифференциация замедленна. Одновременно снижается активность NO-синтазы в стенке сосудов и слизистой. Автор полагает, что увеличение содержания сенсибилизованных Т-лимфоцитов влияет на процессы пролиферации — дифференциации эпителиоцитов, а изменение содержания NO — нарушает деятельность сосудов, что усугубляет тяжесть патологического процесса. Ключевые слова: гиперчувствительность замедленного типа, репарация, слизистая, NO-синтаза. FEATURES during the process of regeneration of oral mucosa INJURY RATS, develops on the background of delayed type hypersensitivity V. N. Pochtar Ukrainian Research Institute of Dental Academy of Medical Sciences Ukraine The author conducted a pilot study of the peculiarities of reparative processes buccal mucosa in 60 rats with delayed-type hypersensitivity. The results showed that the repair processes are changing in relation to the control: higher proliferative activity and differentiation of slowing down. Simultaneously decreased NO-synthase activity in the vascular wall and mucosa. The author believes that the increase of sensitized T-lymphocytes affect the processes of proliferation - differentiation of epithelial cells and the change in NO content - violates the activities of the vessels, which contributes to the severity of the pathological process. Keywords: delayed type hypersensitivity, repair, mucous, NO-synthase.